Is age‐related sarcopenia a real concern for my developing country?. Issue 6 (12th October 2022) - Boshnjaku, Arben
Abstract: Ageing is a distinctive feature of living organisms. With the modernization of human societies, including the development of science, technology and education, expected life expectancy at birth is being extended. This allows novel health‐related conditions to gain particular interest amongst the field experts. Along comes sarcopenia, an age‐related condition of global proportions that effects all populations, societies and countries. Several international working groups have been trying to identify the more appropriate and applicable sarcopenia definition and diagnostic criteria to follow. Contrary to the initial muscle mass‐related context, the shift of attention to muscle strength by the revised European Working Group in Sarcopenia for Older People (EWGSOP2) was ground‐breaking and potentially game‐changing. The suggested diagnostic algorithm by the EWGSOP2 for case finding, diagnosing and quantifying the severity of cases further facilitated the applicability on clinical practices. Since being directly related to the ageing process, sarcopenia presents an issue of growing concern particularly within the high‐income and developed world regions that are generally characterized with an increased life expectancy. In contrast, the developing world and their generally lower life expectancy do not always have sarcopenia amongst the top targeted health‐related concerns. In such cases, the expected life expectancy and the populations' quality of life do not necessarily present an issue of major interest. Other serious medical concerns of acute state often eclipse the need for long‐term health‐related investments, shifting the interest towards only direct interventions and short‐term planning. In conclusion, the emerging of sarcopenia as a serious age‐related concern is finding care providers and healthcare systems from lower and middle‐income countries (LMICs) unprepared. For the time being, it needs to be introduced and promoted in the developing world as a condition with direct life‐threatening implications. Simple and creative forms of approach should be ideated and implemented in both scientific and clinical contexts (by researchers and care providers, respectively). The best practice to address this situation would be by empowering intradisciplinary and interdisciplinary collaborations, as well as facilitating interconnections between researches, healthcare practitioners and clients. This should help establish sarcopenia as a serious age‐related condition that needs a multidisciplinary and multidimensional approach.